Development and Evaluation of the Dynamic Left Turn Intersection. (July 2023) - Hummer, Joseph E.; Milazzo, Joseph S.; Galloway, Jason; Spencer, David; Topp, Andrew; Chapman, Jeremy R.
Dual left turn lanes are typically operated with protected left turn signals, which means extra delay during non-peak hours compared to permissive operation. To reduce this delay, the authors designed, installed, and tested a "dynamic left turn intersection" (DLTi), which is a new way to operate dual left turn lanes. With DLTi, the both lanes are operated with protected phasing during the peak hours when higher capacity is needed, and only the leftmost left turn lane remains open for protected-permissive operation during off-peak hours. The test showed substantial delay savings, the crash experience has been minimal, and the public comments received have been predominantly negative but not overwhelming. Around 85 percent of left-turning motorists complied when the rightmost left turn lane was closed. The team believes that the DLTi test has been a success, and that agencies should begin searching for other suitable locations for DLTi installation.